The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1111/j.1151-2916.1969.tb09181.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Stress Analysis of WC‐Co Cermets: I, Procedures

Abstract: The factors that influence the measurement of stress by the "two-exposure" X-ray diffractometer technique in the WC phase of WC-Co cermets were studied. Chromium Ka radiation was used on the (1072) line of WC (20=135.8"). The X-ray values of Young's modulus and Poisson's ratio are 105x10' psi and 0.19, respectively, and the X-ray stress factor is 1.51 X 10' psi/A. The measured stresses are biaxial. Because penetration is limited to less than 5 pm for CrKa radiation, extreme care in surface preparation and heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Alternatively, a small crack may have formed, but it may then have been polished away during the subsequent material removal step, or the crack size may have been significantly reduced such that the naturally occurring flaws in the material remained dominant. Over the years, several studies [5,8,22,23,48] have shown that the surface region of WC-Co materials can contain a residual compressive stress and that the magnitude of this stress depends on the surface treatment. Residual stresses as low as a few hundred megapascals, but as high 2-3 GPa, have been measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, a small crack may have formed, but it may then have been polished away during the subsequent material removal step, or the crack size may have been significantly reduced such that the naturally occurring flaws in the material remained dominant. Over the years, several studies [5,8,22,23,48] have shown that the surface region of WC-Co materials can contain a residual compressive stress and that the magnitude of this stress depends on the surface treatment. Residual stresses as low as a few hundred megapascals, but as high 2-3 GPa, have been measured.…”
Section: Resultsmentioning
confidence: 99%
“…While this did not improve the ability to measure the crack size, it did provide a marker for the precrack location during the post-test measurement. Heat tinting for 1 h in air at 300°C prior to fracture, as described by Sigl and Exner [48], was the other method attempted. This method highlighted the entire precrack quite nicely.…”
Section: Resultsmentioning
confidence: 99%
“…However, WC-Co cemented carbides are comprised of two consolidated phases with a large difference in their thermal expansion coefficients, thus, they likely accumulate high residual stresses while cooling down to room temperature. Consequently, a substantial amount of research has been conducted on measuring the residual stress of WC-Co cemented carbides in recent years [1][2][3][4][5]. Such measurements are extremely important for the safety assessment of critical structural components and the influence of cutting tool life [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, diffraction can also be used to measure the relative variation of singlephase specific stress or strain upon loading. Diffraction measurements of residual thermal stresses have been performed by different authors [3][4][5][6][7][8] both by X-rays and neutrons. At room temperature, compressive residual stresses around 0.5 GPa are expected in WC and tensile stresses around 2 GPa are expected for cobalt in a WC-18vol.%Co [8].…”
Section: Introductionmentioning
confidence: 99%